Implementing Blockchain Technology for Secure Data Transactions in Cloud Computing Environments Challenges and Solutions - Dandu Varalakshmi; N Shirisha; K Suresh; Saidhbi Shaik; V Venkatesh; C F Theresa Cenate (ITM Web of Conferences)
Security risks in modern multi-cloud environments include data compromise, unauthorized pain points, and increased data leakage risk. We note that while existing security frameworks such as security standards may be useful: they fail to deal with limitations in areas such as privacy, authentication, and secure transactions across multiple cloud platforms. In this paper, we design an optimized, cloud-based blockchain-enabled security framework for real-world scalability, performance, and regulatory constraints. The main innovation consists of a light and energy-saving blockchain construct that minimizes computing overhead and is sustained by an AI-based anomaly detection algorithm to achieve real-time threat mitigation using built-in smart contracts. It also includes quantum-resilient cryptographic algorithms, which provide protection against potential future quantum attacks. Moreover, the use of smart contracts for decentralized identity management minimizes single points of failure, allowing for strict access controls to share the data as needed in a secure manner. The framework naturally integrates with major cloud service providers while being GDPR, HIPAA, and SOC 2 complaint to alleviate regulatory burden. According to experimental results, our model achieves a processing time reduction of 30%, a transaction verification speed gain of 50%, and an energy usage savings of 40% over traditional blockchain frameworks. Another example in the form of an healthcare cloud case study affirms the approach and shows that sensitive medical data is supremely protected from cyberattacks and unauthorized changes. This research highlights the future presage regarding the utilization of blockchain technology in cloud infrastructures to secure trust, transparency, and resiliency against advancing cybersecurity threats. As it resolves key issues surrounding multi-cloud adoption and interoperability, it sets the stage for forward-facing developments, including artificial intelligence-enabled security automation and quantum-resilient cloud storage, ultimately creating a more secure and streamlined cloud landscape. This security framework pave the way to industry ubiquitous multi-cloud adoption that is reliable and safeguard critical assets around the globe.